Content analysis of studies conducted in Iran and abroad on family training sessions concerning educational components - Shahsavari, Mahdiyeh; Sabahizadeh, Mahmood; Nami, Kolsom; Ghourchian, Nadergholi (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of this study was to analyze the content of research conducted in the country and abroad in the field of family education in terms of attention to the components of education. Method: The research method is descriptive-analytical. In order to fulfill the purpose of the research, among the 36 researches conducted, 32 researches about the content of the family education program were analyzed. The tool of data collection is to observe documents and prepare a preliminary list, and to extract and collect the required information, it was from "flashing". Data analysis method was Shannon entropy. Results: The results showed that the highest importance coefficient was related to the "Educational and Academic Education" component with a coefficient of 0.35 and the lowest importance coefficient was related to the "Sexual Education" component with an importance coefficient of 0.19. The values of information load and importance coefficient obtained from the normalized data, in relation to the components of religious-moral education dimension, the highest importance coefficient (0.35) is related to the component of "doing the religious duties of the youth"; In relation to the components of socio-cultural education, the highest importance coefficient (0.37) is related to the category of "socialization and socialization process"; In relation to the components of educational training, the highest coefficient of importance (0.4) is related to the category of "academic problems"; In relation to the components of health education, the highest importance coefficient (0.52) is related to the category of "hygiene principles and health education"; In relation to the components of sexual education, the highest importance coefficient (0.49) is related to the category "familiarity with high-risk situations and puberty and sexual hygiene". Conclusion: Paying attention to the necessity of family education in order to increase the knowledge, information and awareness of parents is inevitable. Therefore, it seems that the parents of the students realized the educational errors in their lives by educating the family and from then on, in the case of increasing knowledge and its effect on the belief system, they will consciously train the flowers of the garden. They act in their lives.